2005
DOI: 10.1258/0022215054516214
|View full text |Cite
|
Sign up to set email alerts
|

An audit of clinical resources available for the care of head and neck cancer patients in England

Abstract: Major changes in service configuration are likely to be required if the current national targets of time to diagnosis and treatment are to be met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…They conclude that major changes in service configuration were likely to be required if the current national targets of time to diagnosis and treatment were to be met. 52 The MDT has become more and more an integral part of the clinical pathway for a patient with HN cancer in many European countries. 53 An audit and re-audit of a rapid-access HN lump clinic with the provision of immediate FNAC assessment and reporting (Ôone-stopÕ clinic) found that over two-thirds of 245 patients referred to the clinic were managed during only one visit each.…”
Section: Quality Control and Auditmentioning
confidence: 99%
“…They conclude that major changes in service configuration were likely to be required if the current national targets of time to diagnosis and treatment were to be met. 52 The MDT has become more and more an integral part of the clinical pathway for a patient with HN cancer in many European countries. 53 An audit and re-audit of a rapid-access HN lump clinic with the provision of immediate FNAC assessment and reporting (Ôone-stopÕ clinic) found that over two-thirds of 245 patients referred to the clinic were managed during only one visit each.…”
Section: Quality Control and Auditmentioning
confidence: 99%
“…oncologists and pathologist having several site-specific meetings to attend. 24 Constraints of job plans.…”
mentioning
confidence: 99%
“…1,9 In the modern era of medicine, cost-effectiveness is an increasing issue with clinicians often having to justify interventions on this basis. [10][11][12] It certainly seems within the UK that a more selective approach to EUAP is gradually developing; although this may, in part, be due to financial restrictions, there is certainly a medical evidence-base to support this move. It is likely that, as this body of evidence increases, the move away from the routine use of EUAP in all patients with oral cavity and oropharyngeal SCC will continue leaving it as a selective screening tool for high-risk individuals or those who present in a symptomatic manner.…”
Section: -5mentioning
confidence: 99%